The role of cultural values on transformational leadership and citizenship behavior - Daria Gom; Lew, Tek Yew; Geoffrey Harvey Tanakinjal; Mary Monica Jiony; Ruth Sikopit Siganul (Medwell Journals, 2017)
Transformational leadership and organizational citizenship behavior (OCB) have gained much popularity in recent years among scholars and practitioners. Although the cultural context of transformational leadership and OCB has increasingly been recognized as highly relevant, there is a paucity of studies done so far. Various research suggested that transformational leaders modifies subordinates OCB that may produce positive behaviors and increase organizational effectiveness. However the impact and process may vary in a different cultural setting. The purpose of this paper is to propose a conceptual framework on the relationship between transformational leadership behavior and citizenship behavior in an integrative way by viewing Sabah ethnic cultural values as a latent moderating mechanism that may not have been empirically tested in the leadership and OCB literature.